(untitled) (The Pakistan Development Review, 2000)
This study is undertaken to test whether or not there exists gender bias in health care utilisation of sick children in Pakistan. Overall, the results are encouraging, as medical consultation has been sought for by a very high proportion (79 percent) of sick children. Moreover, there do not appear to be significant differences by gender in health care utilisation, be it curative or preventive. This is so in spite of the fact that many studies on various gender-related issues in Pakistan have generally shown significant gender bias in favour of male children. Thus one may conclude that parental altruism prevails at least in the provision of health care to sick children. However, the extent and magnitude of effect varies by geographical, socio-economic, and demographic characteristics of the mother. In view of these findings, efforts should be made to minimise gender differentials among various categories of people so that children living in any circumstances may have equal opportunity of health care utilisation. This will be possible when health care facilities are easily accessible to all. The Lady Health Workers Programme of the Government of Pakistan is a major positive step in this regard. Under this programme, health care facilities are provided at people’s door-step. The expansion of this programme will be extremely beneficial in helping parents to provide health care facilities to sick children, both male and female.